Transforming Philanthropic Literacy on the Front Line: Integrating Cash Waqf Values into Marriage Guidance Services for the Productive Generation - Toni Kurnia Jaya (JURNAL ILMIAH GEMA PERENCANA, 2026)
This policy paper is motivated by an anomalous phenomenon in the Islamic philanthropy sector in Lampung Province, namely the significant gap between the high number of annual marriages and the low realization of accumulated cash waqf funds from prospective brides and grooms. The main problem is identified as the low ratio of public participation that is not commensurate with demographic potential, which is rooted in weak cash waqf literacy among the productive age population due to the lack of social environmental influence and the limited reach of adaptive counseling for the younger generation. The methodology used in this policy study is a qualitative-descriptive approach with document analysis and field observation, which is then evaluated using the William N. Dunn policy scoring method based on the criteria of effectiveness, feasibility, and impact to determine intervention priorities. The results of the analysis indicate that the main root of the problem lies in the inconsistency of educational narratives and the low specific competencies of apparatus on the front line of service. Therefore, this article recommends policy transformation through the issuance of the "Decree of the Head of the Lampung Ministry of Religious Affairs Regional Office concerning the Standardization of Marriage Guidance Curriculum (Bimwin) Based on Philanthropic Literacy". These recommendations include the integration of persuasive educational modules, the use of transparent digital tools, and a competency certification scheme for marriage registrars and counselors.